RESULTS OF CLINICAL AND INSTRUMENTAL STUDY OF DIGITAL OCCLUSION INDICES DURING REGISTRATION OF INTERMAXILLARY INTERCUSPAL POSITION IN PATIENTS WITH UNILATERAL DEFECTS AND INTACT DENTITIONS - Т.R. Hlushko; Yu.V. Vovk; V.Yu. Vovk; P.S. Kryukov (Український стоматологічний альманах, 2021)
Introduction. Determination of the patients’ dentitions ratios is an important in the orthopedic dental treatment of defects of the dentofacial system (DFS).